Maturity-onset diabetes of the young secondary to HNF1B variants (HNF1B-MODY): a series of 10 patients from a single diabetes center - Sara Amaral; Ana Palha; Paula Bogalho; José Silva-Nunes (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Maturity-Onset Diabetes of the Young (MODY) is an autosomal dominant condition and represents 1–5% of all cases of diabetes mellitus. MODY is often misdiagnosed as type 1 or type 2 diabetes. The rare subtype 5 (HNF1B-MODY) is due to hepatocyte nuclear factor 1β (HNF1B) molecular alteration and is remarkable for its multisystemic phenotypes characterized by a broad spectrum of pancreatic and extra-pancreatic clinical manifestations. Methods Retrospective study of patients with HNF1B-MODY diagnosis followed in the Centro Hospitalar Universitário Lisboa Central (Lisbon, Portugal). Demographic data, medical history, clinical and laboratory data, follow-up and treatment procedures were obtained from electronic medical records. Results We found 10 patients with HNF1B variants (7 index cases). The median age at diabetes diagnosis was 28 (IQR 24) years and the median age at HNF1B-MODY diagnosis was 40.5 (IQR 23) years. Six patients were initially misclassified as type 1 and 4 as type 2 diabetes. The average time between diabetes diagnosis and the diagnosis of HNF1B-MODY was 16.5 years. Diabetes was the first manifestation in half of the cases. The other half presented with kidney malformations and chronic kidney disease at pediatric age as the first manifestation. All these patients were submitted to kidney transplantation. Long-term diabetes complications included retinopathy (4/10), peripheral neuropathy (2/10) and ischemic cardiomyopathy (1/10). Other extra-pancreatic manifestations included liver test alterations (4/10) and congenital malformation of the female reproductive tract (1/6). History of a first-degree relative with diabetes and/or nephropathy diagnosed at a young age was present in 5 of the 7 index cases. Conclusions Despite being a rare disease, HNF1B-MODY is underdiagnosed and often misclassified. It should be suspected in patients with diabetes and CKD, especially when diabetes appears at a young age, a family history is present, and nephropathy appears before/shortly after the diagnosis of diabetes. Presence of unexplained liver disease increases the degree of suspicion for HNF1B-MODY. Early diagnosis is important to minimize complications and to allow familial screening and pre-conception genetic counseling. Trial registration not applicable due to the retrospective nature of the study, non-interventional.